Use of monoclonal antibodies against Rickettsia tsutsugamushi Kawasaki for serodiagnosis by enzyme-linked immunosorbent assay. - Furuya, Y (1991)
Monoclonal antibodies (MAbs) against Rickettsia tsutsugamushi Kawasaki were prepared. The crossreactivity tests of the MAbs performed by using antigenically distinct strains of R. tsutsugamushi in immunofluorescence and immunoblotting analyses indicated that the Kawasaki strain contains a strain-specific epitope and also contains a common epitope on the 56-kDa polypeptide cross-reactive with the Gilliam strain, group- and subgroup-specific epitopes on the 46-kDa polypeptide, and a subgroup-specific epitope on the 25-kDa polypeptide. By using the strain-specific MAb for serodiagnosis of tsutsugamushi disease (or scrub typhus fever), we have established a method which was designated the inhibition enzyme-linked immunosorbent assay. The principle of the method is to measure the percentage of inhibition of antigen absorption on a MAb-coated plate by antibody-positive sample sera which were mixed with the antigen suspension. The advantages of this test for practical use are that (i) crude antigen can be used, i.e., purification of the antigen is not required; (ii) the test is more sensitive than immunofluorescence; (iii) the final judgment of plus or minus is clear-cut; and (iv) rickettsial antigenic types in the patients can be distinguished by this test.